The prisoner as testimonialista a book review of Bobby V. Villagracia’s Selda Dos (Manila City Jail) - Moratilla, Noel Christian A. (2019)
Access online through this link: https://www.plarideljournal.org/article/the-prisoner-as-testimonialista-a-book-review-of-bobby-v-villagracias-selda-dos-manila-city-jail
Keywords: Villagracia, Bobby V; Books -- Reviews; Bilibid Prison